2015
DOI: 10.1002/2015gl063290
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advection on stratification and chlorophyll variability in the equatorial Pacific

Abstract: Previously reported global‐scale correlations between interannual variability in upper ocean stratification and chlorophyll a (a proxy for phytoplankton biomass) have been shown to be driven by strong associations between the two properties in the central and western equatorial Pacific. Herein, we present evidence that these correlations are not causal but instead result from the advection of heat, salt, and nutrients in the region. Specifically, we demonstrate that stratification and chlorophyll are simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…SST is often used as index of physical changes within the surface mixed layer including its vertical extension, having been used to identify permanently stratified zones [Behrenfeld et al, 2006[Behrenfeld et al, , 2008O'Malley et al, 2010; Gonz alez Taboada and Anad on, 2014] characterized by low primary productivity. However, this approach has been reported to be subjected to several caveats, since SST changes cannot be solely attributed to shoaling or deepening of the MLD at synoptic scales and is influenced by mesoscale processes and horizontal advection [Carranza and Gille, 2015;Dave and Lozier, 2015].…”
Section: Stri R : a Good Measure Of Stratification?mentioning
confidence: 99%
See 1 more Smart Citation
“…SST is often used as index of physical changes within the surface mixed layer including its vertical extension, having been used to identify permanently stratified zones [Behrenfeld et al, 2006[Behrenfeld et al, , 2008O'Malley et al, 2010; Gonz alez Taboada and Anad on, 2014] characterized by low primary productivity. However, this approach has been reported to be subjected to several caveats, since SST changes cannot be solely attributed to shoaling or deepening of the MLD at synoptic scales and is influenced by mesoscale processes and horizontal advection [Carranza and Gille, 2015;Dave and Lozier, 2015].…”
Section: Stri R : a Good Measure Of Stratification?mentioning
confidence: 99%
“…The problem is that no such relationship exists at longer, decadal time-scales [Lozier et al, 2011]. Besides, it has been shown that global-scale correlations between upper ocean stratification and chlorophyll a are driven by strong associations between the two properties in the central and western equatorial Pacific [Dave and Lozier, 2013], and that these correlations are not due to SST changes but result from the advection of heat, salt, and nutrients in the region [Dave and Lozier, 2015].…”
Section: Biogeochemical Implicationsmentioning
confidence: 99%
“…Even though, the percent of total affected areas are relatively similar between CP and EP El niño events, the regional differentiation is marked, and may be of opposing sign (e.g., along the coast of Peru and Chile, the Benguela upwelling, the Great Barrier Reef), or affected during an EP event but not during a CP event (e.g., in the tropical eastern and western Pacific). Several process-orientated studies have further highlighted the important role played by horizontal processes (together with vertical processes) in the supply of nutrients in the surface layer, and specifically demonstrated significant impacts in Winter new primary production in the North Pacific transition zone (Ayers and Lozier, 2010), interannual variations of chlorophyll concentration in the Equatorial Pacific (Gierach et al, 2012;Messié and Chavez, 2013;Dave and Lozier, 2015) and the Red Sea , and decadal variations in phytoplankton abundance in the North Atlantic Subpolar Gyre (Martinez et al, 2015). Thus, both the development of statistical methods to study climate impact, and the assessment of the future evolution of regional physical forcing processes may help us to understand phytoplankton responses to climate change and improve confidence in our projection of future ecosystem state Boyd et al, 2014).…”
Section: Implications For Climate Impact Researchmentioning
confidence: 99%
“…Somewhat expected, the EQP has very little seasonal variability, crossing the border between FU=2 and 3 across the seasons. Here, nutrients are horizontally advected to this region (Dave and Lozier 2015), causing higher biomass and greener waters. Our data suggests that this process is somewhat higher during the boreal summer, leading to a slight seasonal cycle.…”
Section: Seasonal Variability Of Selected Marine Areasmentioning
confidence: 99%